Pulmonary embolism with floating right atrial thrombus successfully treated with streptokinase: a case report. (December 2016) - Nasrin, Sahela; Cader, Fathima; Salahuddin, Md.; Nazrin, Tahera; Shafi, Masuma
Abstract Background Massive pulmonary embolism (PE) is associated with significant mortality, especially if compounded by haemodynamic instability, right ventricular (RV) dysfunction and right atrial (RA) thrombus. Thrombolysis can be lifesaving in patients with major embolism and cardiogenic shock, and accelerates the resolution of thrombus. Only three fibrinolytic agents—namely streptokinase, urokinase, and recombinant tissue plasminogen activator (alteplase) have been approved in the treatment of PE, with studies demonstrating similar safety profiles. Case presentation We report the case of a 33-year-old Bangladeshi Bengali female with a history of recent ankle fracture and immobilization, who presented with massive PE, leading to cardiac arrest. Upon rapid resuscitation, urgent echocardiogram revealed RV dysfunction with floating RA thrombus, and she was successfully treated with 1.5 million IU of streptokinase over 2 h as per accelerated regimen recommended by the European Society of Cardiology guidelines, resulting in successful resolution of the right heart thrombus, and significant clinical improvement. Subsequent CT pulmonary angiogram confirmed the diagnosis of PE, and she was anticoagulated to a PT/INR of 2.0–3.0 for 3 months. Conclusions Echocardiography is a suitable alternative for rapid diagnosis of acute massive PE associated with RA thrombus and cardiovascular collapse, especially when a delay to CT pulmonary angiogram may be anticipated, and in the setting of immediate cardio-pulmonary resuscitation. Thrombolysis is a rapid and life-saving therapeutic measure in such cases.